Gestão integrada dos resíduos sólidos urbanos no município de Juazeiro do Norte, Ceará: uma abordagem à luz da política nacional de resíduos sólidos. - Muller, Luiz Neto Paiva e Silva (2016)
An ineffective and inefficient Municipal Solid Waste (MSW) management causes numerous problems, requiring stakeholders the planning of sustainable initiatives in order to mitigate the negative impacts, enhance positive impacts and meet the National Policy of Solid Waste (PNRS). This thesis aims to diagnose and propose solutions for the MSW management in Juazeiro do Norte, Ceará. The methodology is qualitative and quantitative, using some stages of Checkland’s systemic methodology SSM, PNRS settings, quantitative projection techniques, AHP decision-making method, sustainability criteria and secondary information and data. The diagnosis points out that the city of Juazeiro do Norte, in the state of Ceará, has problems of almost no sorting at source, lack of selective collection, inefficiency integration between participants of the production chain and break of the regulatory hierarchy due to the lack of MSW treatment units, causing major negative environmental impacts and a significant loss of solid waste with economic value and potential for job creation. It is estimated that in the next 20 years if nothing is done, the waste collected and buried in the landfill of Juazeiro do Norte in this period, will occupy an area equivalent to 22 soccer fields (153,212 m2) and will emit approximately 159,341 tons of methane and 437,195 tons of carbon dioxide that will extend over the next 40 years. Thus, in order to propose a solution, this study evaluates the results obtained on different criteria (environmental, economic, social, technical and regulatory) in five different MSW treatment alternatives based on good practices present in Brazil and the world and which mix mechanical, biological and thermal treatment plants, being divided into centralized and decentralized models. Based on the results, the alternatives 03 (decentralized sorting centers and anaerobic digesters) and 01 (decentralized sorting centers and composting plants) are the MSW treatment options more favorable to Juazeiro do Norte, with a percentage of 25.11% and 24.97%, respectively. The decentralized alternatives 01 and 03 have an advantage over the centralized alternatives 04, 02 and 05 due mainly to higher job creation and technical feasibility.